Marital Satisfaction and Depression in Mothers of 3-4 Year Old Children with Developmental Delay in Comparison with Mothers of Normal Children - Ahmadi Doulabi, Mahbobeh; Sajedi, Firoozeh; vameghi, Roshanak; Mazaheri, Mohammad Ali; Akbarzaddeh Baghban, Alireza; Afraz, Fatemeh (Iranian Journal of Child Neurology, 2019)
Objectives The present study evaluated the depression and marital satisfaction in mothers of 36-48 months old children with developmental delay in comparison with mothers of normal children. Materials & Methods This cross-sectional study was performed on 616 mothers and their children, aged 36 - 48 months, from Apr 2015 to Feb 2016, in some kindergartens in Tehran, Iran. Participants were selected through multi-stage random sampling. The children were divided according to the developmental status into two groups of normal development and developmental delay. The following instruments were used: A demographic and children specification questionnaire, marital satisfaction scale, the Beck Depression Inventory, and the Ages and Stages Questionnaire. The data were analyzed using SPSS16 software. Independent t-test and Pearson correlation were employed at significance level of 0.05. Results The mean age of children with developmental delay and normal development was 41.94±4.48 and 42.17±5.02 months, respectively. The prevalence of developmental delay in children aged 36-48 months was 17.4% and in normal development children was 82.6%. Developmental delay in boys was 23%. The highest incidence of developmental delays was in fine motor skills. Independent t-test revealed a significant difference between mothers’ depression and marital satisfaction with and without developmental delays (P=0.0001). In addition, the correlation was observed between the mother’s depression and marital satisfaction (P=0.0001). Conclusion Mothers of children with developmental delay suffer more from depression and have less marital satisfaction compared to mothers of healthy children. Interventional studies to reduce depression and increase marital satisfaction and its impact on development status should be conducted. Keywords: Depression; Developmental delay; Marital status; Satisfaction